Take the 2-minute tour ×
Mathematics Stack Exchange is a question and answer site for people studying math at any level and professionals in related fields. It's 100% free, no registration required.

Find the values of the real constants $c$ and $d$ such that

$$\lim_{x\to 0}\frac{\sqrt{c+dx}-\sqrt{3}}{x}=\sqrt{3}$$

I really have no clue how to even get started.

share|improve this question

migrated from mathematica.stackexchange.com Sep 13 '12 at 12:30

This question came from our site for users of Mathematica.

    
Been wondering if I should do a mathematics major if I can't even comprehend a question this simple... –  kingboonz Sep 13 '12 at 9:26
    
Start with Series[Sqrt[c + d x], {x, 0, 1}]/x; how to make this finite and equal to Sqrt[3] in the limit ? –  b.gatessucks Sep 13 '12 at 9:31
1  
This is more of a math question than a Mathematica one, so I'm migrating this to math.SE. –  J. M. Sep 13 '12 at 12:30
    
@J.M. I don't agree, this question is mathematically very simple, however Mathematica hardly tackles this problem. So I find this a valuable Mathematica question and upvoted it. –  Artes Sep 13 '12 at 12:37
    
@Artes, considering the "I realised I posted on the wrong forum" comment... –  J. M. Sep 13 '12 at 12:39
show 2 more comments

3 Answers 3

up vote 4 down vote accepted

I don't know a way Mathematica is going to solve that directly for you, but it can help you understand what happens. First, let's ask it what the general expression for the limit is:

Limit[(Sqrt[c + d*x] - Sqrt[3])/x, x -> 0]

The answer is:

DirectedInfinity[-Sqrt[3] + Sqrt[c]]

So, this limit is an infinity, and has the same sign as $\sqrt c-\sqrt 3$. If you want the limit to be finite, you have only one special case you can try: what happens if $\sqrt c-\sqrt 3=0$, i.e. if $c=3$?

Limit[(Sqrt[3 + d*x] - Sqrt[3])/x, x -> 0]

The results is:

d/(2 Sqrt[3])

which is finite, so all is well. Now, you need this to be equal to $\sqrt 3$, which you can sure solve yourself, but just to be thorough, let's ask Mathematica to do it:

Solve[Limit[(Sqrt[3 + d*x] - Sqrt[3])/x, x -> 0] == Sqrt[3], d]

Conclusion: no silver bullet, but definitely a way to help you understand this equation if your math skills fail you!

share|improve this answer
    
Thanks F'x. You have been an amazing help with the pictures in my questions. I realised I posted on the wrong forum w/e. Thanks anyway!!! –  kingboonz Sep 13 '12 at 9:58
add comment

Method I

Since we have a fraction going to a non-vanishing value given its denominator is going to 0 we have to assume that its numerator also tends to 0, therefore we should solve :

Reduce[Limit[Numerator[(Sqrt[c + d*x] - Sqrt[3])/x], x -> 0] == 0, {c, d}]
c == 3

We could use Solve as well with the option : InverseFunctions -> True, now taking the value into the system we have :

Reduce[ c == 3 && Limit[(Sqrt[3 + d*x] - Sqrt[3])/x, x -> 0] == Sqrt[3], {c, d}]
c == 3 && d == 6

Method II

Another way to tackle the problem is to expand the expression in a power series around x == 0 :

Normal @ Series[ (Sqrt[c + d*x] - Sqrt[3])/x, {x, 0, 3}]

enter image description here

Now you can find limits of every term separately :

Limit[#, x -> 0] & /@ List @@ Normal@Series[(Sqrt[c + d*x] - Sqrt[3])/x, {x, 0, 5}]
{d/(2 Sqrt[c]), (-Sqrt[3] + Sqrt[c]) Infinity, 0, 0, 0, 0, 0}

The only problem comes from the second term, however we can get rid of it by assuming a priori its value by setting c == 3 or simply solving this system :

Solve[ {( -Sqrt[3] + Sqrt[c])/x == 0,  d/(2 Sqrt[c]) == Sqrt[3]}, {c, d}, 
         InverseFunctions -> True]
 {{c -> 3, d -> 6}}
share|improve this answer
add comment

$$\lim_{x\to 0}\frac{\sqrt{c+dx}-\sqrt{3}}{x}=\sqrt{3}$$

Since the denominator goes to $0$, the limit cannot exist unless the numerator also goes to $0$. The numerator is $\sqrt{c+dx}-\sqrt{3}$, so that would have to go to $0$ as $x$ goes to $0$. But it goes to $\sqrt{c+d\cdot0} - \sqrt{3}$. Hence $c+d\cdot0$ must be $3$. That tells you $c$ is $3$, and you've got $$\lim_{x\to 0}\frac{\sqrt{3+dx}-\sqrt{3}}{x}=\sqrt{3}.$$

Now rationalize the numerator: $$ \frac{\sqrt{3+dx}-\sqrt{3}}{x} = \frac{\left(\sqrt{3+dx}-\sqrt{3}\right)\left(\sqrt{3+dx}+\sqrt{3}\right)}{x\left(\sqrt{3+dx}+\sqrt{3}\right)}= \frac{dx}{x\left(\sqrt{3+dx}+\sqrt{3}\right)}. $$ The $x$s cancel and we get $$ \frac{d}{\sqrt{3+dx}+\sqrt{3}}. $$ The limit of that as $x\to0$ is $d/(2\sqrt{3})$. So you want $d/(2\sqrt{3}) = \sqrt{3}$. Multiply both sides by $2\sqrt{3}$ and you get $d=6$.

share|improve this answer
add comment

Your Answer

 
discard

By posting your answer, you agree to the privacy policy and terms of service.

Not the answer you're looking for? Browse other questions tagged or ask your own question.